2018
DOI: 10.1103/physrevb.98.045104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast terahertz field control of electronic and structural interactions in vanadium dioxide

Abstract: Vanadium dioxide, an archetypal correlated-electron material, undergoes an insulator-metal transition near room temperature that exhibits electron-correlation-driven and structurally-driven physics. Using ultrafast optical spectroscopy and x-ray scattering we show that these processes can be disentangled in the time domain. Specifically, following intense sub-picosecond electric-field excitation, a partial collapse of the insulating gap occurs within the first ps. Subsequently, this electronic reconfiguration … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Therefore, we conclude that after PIPT the VO 2 film expands along the rutile axis during a short time~a/s and then slowly shrinks. Such non-monotonic behavior has been observed earlier in some electron diffraction experiments [46][47][48][49][50][51] .…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, we conclude that after PIPT the VO 2 film expands along the rutile axis during a short time~a/s and then slowly shrinks. Such non-monotonic behavior has been observed earlier in some electron diffraction experiments [46][47][48][49][50][51] .…”
Section: Discussionsupporting
confidence: 76%
“…Electrons and/or phonons may also form a nonequilibrium distribution within the respective subsystem, which cannot be characterized by an effective temperature [19][20][21]. Significant progress has been recently achieved in the understanding of nonequilibrium states of electrons and phonons at nanoscale [22][23][24][25][26]. However, a comprehensive microscopic understanding of current-induced thermal energy generation and transport has not yet emerged.…”
mentioning
confidence: 99%
“…The ultrafast IMT triggered by the fs pump laser extensively broadens the applications based on VO 2 , making VO 2 a promising candidate for high-speed THz modulators [ 58 ]. Except for the mentioned thermal and fs laser-based approach, recent efforts have shown that electrical field [ 59 , 60 , 61 , 62 , 63 ], continuous-wave (CW) laser [ 64 , 65 , 66 ], intense THz field [ 67 , 68 , 69 ] and electrochemical modification [ 70 , 71 , 72 ] can also provide effective control of IMT, and all these approaches can be integrated into THz devices.…”
Section: Introductionmentioning
confidence: 99%